2016
DOI: 10.1177/2167702616644894
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Depressive Symptoms Following Consecutive Pregnancies

Abstract: Postpartum depression is a major mental health issue for women and society. We examined stability and change in symptoms of depression over two consecutive pregnancies and tested life stress as a potential mechanism. The Community Child Health Network followed an ethnically/racially diverse sample from one month after a birth for two years. A subset of 228 women had a second birth. Interview measures of depression symptoms (EPDS) and life stress (life events, perceived stress, chronic stress, interpersonal agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 53 publications
(61 reference statements)
1
7
0
1
Order By: Relevance
“…Third, data on the length of interpregnancy intervals as well as on a whether or not women gave birth to a living child between the pregnancy loss and the current pregnancy were not available, and we were therefore unable to test the moderating effects of these variables. Previous studies suggest that the length of the inter-pregnancy interval does not affect the association between history of prenatal loss and depression and/or anxiety during a subsequent pregnancy or in the postpartum period (Gravensteen et al, 2018;Schetter, Saxbe, Cheadle, & Guardino, 2016). A large longitudinal cohort study reports a robust association between history of prenatal loss with increased levels of anxiety and depression during a subsequent pregnancy, which remained stable across the pre-and postnatal period of the index pregnancy, thereby indicating that the psychological impairment associated with previous prenatal loss might not attenuate significantly following the birth of a living child (Blackmore et al, 2011).…”
Section: Psychological Medicinementioning
confidence: 99%
“…Third, data on the length of interpregnancy intervals as well as on a whether or not women gave birth to a living child between the pregnancy loss and the current pregnancy were not available, and we were therefore unable to test the moderating effects of these variables. Previous studies suggest that the length of the inter-pregnancy interval does not affect the association between history of prenatal loss and depression and/or anxiety during a subsequent pregnancy or in the postpartum period (Gravensteen et al, 2018;Schetter, Saxbe, Cheadle, & Guardino, 2016). A large longitudinal cohort study reports a robust association between history of prenatal loss with increased levels of anxiety and depression during a subsequent pregnancy, which remained stable across the pre-and postnatal period of the index pregnancy, thereby indicating that the psychological impairment associated with previous prenatal loss might not attenuate significantly following the birth of a living child (Blackmore et al, 2011).…”
Section: Psychological Medicinementioning
confidence: 99%
“…Fuller (2014), Currie and Rossin‐Slater (2013), and Simeonova (2011) estimate the negative effects of natural disasters on pregnancy outcomes. Physiologically, pregnancy stress has been associated with low birth weight and earlier delivery (Lobel, Dunkel Schetter, & Scrimshaw, 1992) and increased likelihood of depressive symptoms in the postpartum period for both parents (Dunkel Schetter et al., 2016; Saxbe et al., 2015). Webb, Siega‐Riz, and Dole (2009) find evidence of relationship between depression and gestational weight gain, but find no similar relationship with stress and anxiety.…”
Section: Literature On Environment and Maternal Healthmentioning
confidence: 99%
“…Pregnancy and the postpartum are associated with dramatic changes in reproductive steroids, and there is very clear evidence that the postpartum is associated with depression for many women. For example, based on a meta analysis of n = 59 studies, it has been estimated that approximately 13% of women experience postpartum depression (O’Hara & Swain, 1996), and recent research has shown that individual levels of postpartum depression show recurrent stability across at least two subsequent pregnancies (Dunkel Schetter, Saxbe, Cheadle, & Guardino, 2016). Moreover, experimental research using a pharmacological simulation of steroid changes associated with pregnancy and parturition has provided clear evidence for a causal role of estrogen and progesterone in triggering postpartum depression (e.g., the pharmacological simulation triggered depressive symptoms among women with a history of postpartum depression, but not among those with no history; Bloch et al, 2000).…”
Section: Reproductive Life Eventsmentioning
confidence: 99%